2016
DOI: 10.1080/15384101.2016.1192731
|View full text |Cite
|
Sign up to set email alerts
|

PGRMC1 participates in late events of bovine granulosa cells mitosis and oocyte meiosis

Abstract: Progesterone Receptor Membrane Component 1 (PGRMC1) is expressed in both oocyte and ovarian somatic cells, where it is found in multiple cellular sub-compartments including the mitotic spindle apparatus. PGRMC1 localization in the maturing bovine oocytes mirrors its localization in mitotic cells, suggesting a possible common action in mitosis and meiosis. To test the hypothesis that altering PGRMC1 activity leads to similar defects in mitosis and meiosis, PGRMC1 function was perturbed in cultured bovine granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
46
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 59 publications
5
46
0
1
Order By: Relevance
“…We show that changes in posttranslational modification of PGRMC1 are involved in the maintenance of genomic integrity. Future research should examine whether this involves previously reported PGRMC1 involvement with G0/G1 checkpoint and/or spindle association (Cahill et al, 2016a;Griffin et al, 2014;Juhlen et al, 2018;Luciano and Peluso, 2016;Terzaghi et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We show that changes in posttranslational modification of PGRMC1 are involved in the maintenance of genomic integrity. Future research should examine whether this involves previously reported PGRMC1 involvement with G0/G1 checkpoint and/or spindle association (Cahill et al, 2016a;Griffin et al, 2014;Juhlen et al, 2018;Luciano and Peluso, 2016;Terzaghi et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Progesterone (P4) Receptor Membrane Components 1 (PGRMC1) is a cytochrome b5 (cytb5) protein and a member of the membrane-associated P4 receptor (MAPR) family with a plethora of cellular functions. These include some cytb5-typical functions that predate or are potentially ancient in eukaryotes (regulation of heme synthesis (Piel et al, 2016), cyP450 (cytochrome P450) interactions (Oda et al, 2011;Ryu et al, 2017;Szczesna-Skorupa and Kemper, 2011), sterol metabolism (Cahill and Medlock, 2017;Hughes et al, 2007;Mallory et al, 2005)), some that evidently arose in eukaryotes (membrane trafficking (reviewed by: Cahill et al, 2016a;Mifsud and Bateman, 2002), cell cycle regulation at the G0/G1 checkpoint (Cahill et al, 2016a;Griffin et al, 2014;, mitotic/meiotic spindle association (Juhlen et al, 2018;Luciano and Peluso, 2016;Terzaghi et al, 2016)), and clearly specialized metazoan functions including e.g., fertility, embryogenic axon guidance, and membrane trafficking associated with synaptic plasticity (reviewed by: Cahill et al, 2016a;Rohe et al, 2009). CyP450-interactions (Ryu et al, 2017) conspicuously feature PGRMC1 regulation of the most conserved eukaryotic cyP450 (lanosterol 14-alpha demethylase, CYP51A) to modify the first sterol (lanosterol) from yeast to mammals (Cahill, 2007;Hughes et al, 2007;Mallory et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Before using Aurora B phospho-(Thr232), two other antibodies (anti-Aurora B and anti-CENPA) did not produce a centromeric stain. Notably, anti-Aurora B and anti-CENPA were already successfully used in bovine and human cells 26,27,28 ; therefore, it was concluded that they were not specific to the horse. This technique can also be limited by the availability of a confocal laser scanning microscope and image analysis software.…”
Section: Discussionmentioning
confidence: 99%
“…Its subcellular localization can be cytoplasmic, nuclear/nucleolar, mitochondrial, endoplasmic reticulum, cytoplasmic vesicles, or extracellular (Cahill et al, 2016a;Riad et al, 2018;Ryu et al, 2017). It is involved in cell cycle processes at the G1 checkpoint and during mitosis (Luciano et al, 2010;Luciano and Peluso, 2016;Peluso et al, 2014;Sueldo et al, 2015;Terzaghi et al, 2018;Terzaghi et al, 2016), and elevated PGRMC1 expression has been associated with poor prognosis in multiple types of cancer (Ahmed et al, 2010;Cahill et al, 2016a;Losel et al, 2008;Rohe et al, 2009;Ruan et al, 2017;Shih et al, 2019;Willibald et al, 2017).…”
Section: Introductionmentioning
confidence: 99%